THE ROLE OF USING BRAINSTORMING METHOD IN TEACHING ENGLISH LANGUAGE TO STUDENTS (as an example of non-philological education) (Scientific journal of the Fergana State University, 2024)
This article illustrates the importance of brainstorming and general brainstorming methods for non-philological students, modern educational methods, and the extent to which lessons are effective for students.